Faktor-Faktor Stres Pekerjaan Pensyarah Politeknik : Satu Kajian Kes Di Politeknik Sultan Abdul Halim Mu'adzam Shah - Wan Mohamad Nasir, Wan Abdul Rahman (2002)

(untitled)
The purpose of this study is to identify the level of stress among the polytechnic lecturers based on demographic factor (which includes gender, length of service, academic qualification and departments which lecturers are attached to). It also aims to explain the level of stress in relation to stress factors which are conflict of role, ambiguity of role, workload, climate and organizational relationship and career development factors. The survey was carried out in Polytechnic Sultan Abdul Halim Mu'adzam Shah (POLIMAS), Jitra, Kedah. 165 lecturers from this politechnic were chosen as sample. Data was collected through 34 item questionnaires constructed on a likert scale. Both descriptive and inferential statistics were used to analyse the data using the SPSS version 10.0. Statistical tools such as t-test and One Way Analysis of Variance (ANOVA) were used to test the hyphotheses. The 0.05 level of significance was used for this study. The findings of this study shows that there are significant differences between gender, departments which the lecturers are attached to and the length of service which the causes of stress being studied. The departments which the lecturers are attached to is found to have significance difference with all the causes of stress namely conflict of role, ambiguity of role, workload, climate and organizational relationship and career development. The overall level of stress of POLIMAS lecturers is average.